2017
DOI: 10.1093/gbe/evx212
|View full text |Cite
|
Sign up to set email alerts
|

FA-SAT Is an Old Satellite DNA Frozen in Several Bilateria Genomes

Abstract: In recent years, a growing body of evidence has recognized the tandem repeat sequences, and specifically satellite DNA, as a functional class of sequences in the genomic “dark matter.” Using an original, complementary, and thus an eclectic experimental design, we show that the cat archetypal satellite DNA sequence, FA-SAT, is “frozen” conservatively in several Bilateria genomes. We found different genomic FA-SAT architectures, and the interspersion pattern was conserved. In Carnivora genomes, the FA-SAT-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 72 publications
(101 reference statements)
2
45
0
Order By: Relevance
“…This observation suggests that the locus evolved in the late Triassic after divergence of the Anophelinae from the Culicinae subfamily of mosquitoes (229-192 mya 33 ), but before further divergence of the culicine genera (226-172 mya 33 ). This establishes this repeat locus as one of the very few ancient and deeply conserved satellite repeats that have hitherto been described 28-30,34 . Conservation of the locus over million years of mosquito evolution strongly suggests important and conserved functions for the locus and its associated piRNAs.…”
Section: Mainmentioning
confidence: 64%
“…This observation suggests that the locus evolved in the late Triassic after divergence of the Anophelinae from the Culicinae subfamily of mosquitoes (229-192 mya 33 ), but before further divergence of the culicine genera (226-172 mya 33 ). This establishes this repeat locus as one of the very few ancient and deeply conserved satellite repeats that have hitherto been described 28-30,34 . Conservation of the locus over million years of mosquito evolution strongly suggests important and conserved functions for the locus and its associated piRNAs.…”
Section: Mainmentioning
confidence: 64%
“…Nevertheless, some satDNAs seem to have been preserved or "frozen" across different taxa during long evolutionary periods [22][23][24] with some of them being transcribed into satellite non-coding RNAs (satncRNAs). Indeed, transcripts of satDNAs have been reported in different species, highlighting a possible role for satncRNAs in the regulation of gene expression, cancer outcomes and aging [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In this repeat monomer, 12 highly conserved CpG sites were found (Kang et al 2001;Yamanaka et al 2011), and these seem to be highly methylated in most tissues (Schnedl et al 1976;Sturm & Taylor 1981;Pagés & Roizés 1982;Adams et al 1983). Additionally, it has been suggested that these satDNAs (like some others: Biscotti et al 2015;Chaves et al 2017) could be transcriptionally active (Su et al 1982), being transcribed by RNA polymerase III.…”
Section: Evolution Of Satdna Families In the Cattle Genome (Bovidae Fmentioning
confidence: 92%
“…However, the systematic and phylogenetic relationships among the various species of this family are still under discussion (Rubes et al 2008;MacEachern et al 2009;Nieddu et al 2015). Nevertheless, the comparative study of the nucleotide sequences and locations of repetitive DNA families in related species is providing information about their own evolutionary mechanisms and the species' evolutionary history, since some repetitive sequences are extremely well conserved between species (Petraccioli et al 2015;Chaves et al 2017), while others are so variable that they can resolve taxonomic issues, defining differences between closely related species (Chaves et al 2000a(Chaves et al , 2005Adega et al 2006).…”
Section: Evolution Of Satdna Families In the Cattle Genome (Bovidae Fmentioning
confidence: 99%
See 1 more Smart Citation